Customer Perceptions of Service Quality in Luxury Hotels in Jordan / Ala`a Nimer AbuKhalifeh and Ahmad Puad Mat Som - AbuKhalifeh, Ala`a Nimer; Mat Som, Ahmad Puad (UiTM Press, 2016)
Providing quality services has become one of the critical issues in the tourism industry, and several studies have been paying attention to it. On the other hand, there seems to be a paucity of research on service quality Jordanian hotels, making it difficult to fashion an appropriate management intervention. There have been insufficient attempts to relate customers' perceptions of service quality to their socio- demographic characteristics as well as the characteristics of organizations delivering the service. This study explores and conceptualize customers' perceptions of service quality in the food and beverage servicedepartment in Jordanian hotels.